(untitled) (The Research of Medical Science Review, 2025)
Background: A number of men with severe erectile dysfunction (ED) fail to benefit from tadalafil, even when given in higher doses. Treatment options in such cases are limited. Bupropion, a non-serotonergic antidepressant, has shown potential benefits for sexual function and may offer an alternative route of treatment. Methods: This was a retrospective review of patients between 25 and 60 years old diagnosed with severe ED who showed little or no improvement with tadalafil. These patients were later prescribed bupropion, either 150 mg or 300 mg daily. After 4-6 weeks, they were followed up to assess improvement in erections, ability to have intercourse, any side effects, and whether they chose to continue treatment. Results: Most patients reported moderate to marked improvement in erection quality, and a good number were able to achieve satisfactory intercourse. Side effects were minimal, with occasional insomnia being the most commonly reported issue. A majority expressed satisfaction with the treatment and showed willingness to continue. Conclusion: Bupropion may be a practical and effective treatment for patients with severe ED who do not respond to PDE5 inhibitors like tadalafil. Further prospective studies are encouraged to confirm these findings.